Comparative evaluation of advanced oxidation processes (AOPs) for reducing SARS-CoV-2 viral load from campus sewage water - Pramanik, Rinka; Bodawar, Narendra; Brahme, Aashay; Kamble, Sanjay; Dharne, Mahesh (Journal of Environmental Chemical Engineering, 2023)
Presence of SARS-CoV-2 in wastewater is a major concern as the wastewater meets rivers and other water bodies and is used by the population for various purposes. Hence it is very important to treat sewage water in an efficient manner in order to reduce the public health risk. In the present work, various advanced oxidation processes (AOPs) have been evaluated for disinfection of SARS-CoV-2 from sewage water collected from STP inlet of academic institutional residential. The sewage water was subjected to ten AOPs, which include Ozone (O3), Hydrodynamic cavitation (HC), Ultraviolet radiation (UV), and their hybrid combinations like HC/O3, HC/O3/ H2O2, HC/H2O2, O3/UV, UV/H2O2, UV/H2O2/O3, and O3/H2O2 to reduce SARS-CoV-2 viral load. Further, AOP treated sewage water was subjected to total nucleic acid isolation followed by RT-qPCR for viral load estimation. The sewage water treatment techniques were evaluated based on their viral concentration-reducing efficiency. It was found that ozone and ozone-coupled hybrid AOPs showed the most promising result with more than 98 % SARS-CoV-2 viral load reducing efficiency from sewage water. Interestingly, the best six AOPs used in this study significantly reduced both the SARS-CoV-2 and PMMoV (faecal indicator) viral load and improved water quality in terms of increasing DO and decreasing TOC.
Keywords: AOPs and hybrid AOPs; Hydrodynamic cavitation; Ozonation; PMMoV; SARS-CoV-2; Sewage water treatment

Degradation of aniline blue dye in aqueous solution using ozonation as advanced oxidation process: optimization and mechanism - Bhawsar, Aastha; Bhutada, Dinesh; Ghuge, Santosh (Journal of the Indian Chemical Society, 2025)
Aniline blue dye is widely used in various fields, including textile dyeing, biotechnological processes, and analytical chemistry research. However, its release into the environment without proper treatment can have serious adverse effects on human health and the ecosystem, emphasizing the need for effective management and remediation strategies. A limited number of studies are available in the literature employing advanced oxidation processes (AOPs) for the mineralization of aniline blue dye. Therefore, the present work explores ozonation as one of the AOPs to study the degradation aniline blue dye in aqueous solution. The experimental parameters like initial dye concentration, inlet ozone dose and initial dye solution pH were optimized in order to maximize aniline blue dye degradation efficiency. The direct and indirect degradation pathways were analyzed using tbutanol as a radical scavenger. The maximum degradation efficiency of 81.1 % was achieved at optimal experimental conditions of initial dye concentration of 250 mg/L, inlet ozone dose of 18g/h and initial dye solution pH 11 after 30 min of ozonation. The complete colour removal was observed after 15 min of ozonation at the optimized experimental conditions. The presence of radical scavenger t-butanol had no impact on colour removal efficiency indicating direct ozone molecule mechanism. However, COD removal efficiency was decreased with the addition of radical scavenger t-butanol suggesting indirect hydroxyl radical based mechanism. The experimental results suggested that ozonation is an effective and promising method for the degradation of aniline blue dye in aqueous solution, showcasing significant potential for its application in wastewater treatment.
Keywords: Aniline blue dye; Degradation mechanism; Ozonation

Recycling textile dyeing effluent through ozonation: an environmentally sustainable approach for reducing freshwater and chemical consumption and lowering operational costs - Deogaonkar-Baride, Smita; Koli, Mitesh; Ghuge, Santosh P. (Journal of Cleaner Production, 2025)
Dyeing operations in textile industries require large quantities of freshwater, which creates handling challenges and generates wastewater with high organic load that is difficult to treat and incurs high treatment costs. Minimizing freshwater consumption is essential for adopting sustainable practices. A limited number of studies are available in the literature exploring the possibility of recycling dyeing effluent through ozonation as an ecofriendly approach. Therefore, in the present work, the recycling of effluents obtained after dyeing with Reactive Red 198 (RR198) and Reactive Blue 21 (RB21) dyes through ozonation treatment has been studied. Nearly complete decolourization with COD removal efficiency of 32 % was obtained for both dye effluents after 15 min of ozonation. The qualities of recycled dyed fabrics were compared to fresh water-dyed fabrics through spectrophotometric analysis and colour fastness tests. These qualities for both dyed fabrics with recycled effluent were found to be either in excellent or good category after each recycle. Comparative analysis of freshwater and chemical requirements, along with cost savings, was conducted over four dyeing attempts. The study revealed significant savings with recycled effluent dyeing including 60 % reduction in fresh water usage and 75 % in salt consumption compared to conventional freshwater dyeing. Thus, recycling textile dyeing effluent through ozonation treatment was found to be a resource efficient approach. This approach not only significantly reduces wastewater volumes but also freshwater demand without compromising the colour-related qualities of dyed fabrics. Additionally, it minimizes operational expenses, thereby, supporting textile industry's shift toward sustainable practices.
Keywords: Chemical saving; Freshwater consumption; Ozonation; Recycling; Textile industry effluent